2013
DOI: 10.1007/s40196-013-0019-2
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership, innovative work behavior, and employee well-being

Abstract: Different studies have shown that transformational leadership, which is categorized as a positive leadership, can increase employee's well-being and innovation. However, the research about the social interactional mechanism used to improve the aforementioned outcomes is scant. This research investigates the mediating roles of leader's active empathetic listening and psychological safety through a survey data collected from 583 postgraduate management students in three top universities in Iran working either fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
52
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 112 publications
12
52
1
1
Order By: Relevance
“…The results of the survey are consistent with the obtained results by Khan et al (2009), etc. Considering the fact that transformational leadership style has an influence on organizational creativity, and organizational creativity has an influence on organizational agility, thus organizational creativity in the influence of transformational leadership style has a mediating role on the organizational agility. Results of this hypothesis is consistent with the results of Mohammadi and Amiri (2013) and Sharifirad et al (2013).…”
Section: Resultssupporting
confidence: 92%
“…The results of the survey are consistent with the obtained results by Khan et al (2009), etc. Considering the fact that transformational leadership style has an influence on organizational creativity, and organizational creativity has an influence on organizational agility, thus organizational creativity in the influence of transformational leadership style has a mediating role on the organizational agility. Results of this hypothesis is consistent with the results of Mohammadi and Amiri (2013) and Sharifirad et al (2013).…”
Section: Resultssupporting
confidence: 92%
“…There is also evidence that leadership involving consideration of others rather than leadership that is task-oriented is related to people-oriented listening behavior (Kluger & Zaidel, 2013). Another study has shown that AEL partly accounts for the relationship between Transformational Leadership and positive outcomes of innovative work and well being in employees (Sharifirad, 2013).…”
Section: Big-5 Traits Assertiveness and Listeningmentioning
confidence: 99%
“…Firstly, they both reflect positive psychological resources within individual from their definition, we know that authentic leadership is a process that draws from leader's positive psychological capacities (Gardner, 2011), and employee well-being also reflects person's positive emotion and positive cognition (Zheng et al, 2015). In addition, other positive form of leadership, for example, transformational leadership, ethical leadership, has been confirmed that it is positively related to well-being (sharifirad et al, 2013;Tu & Lu, 2013). Thus, authentic leadership might also have a certain connection with employee well-being.…”
Section: The Mediating Role Of Employee Well-beingmentioning
confidence: 95%
“…There is also some empirical research support that employee well-being is po- (Sharifirad, 2013). Generally speaking, employee who owns positive psychological resources or happy feelings would usually lead to constructive behavior (Nordin et al, 2012).…”
Section: The Mediating Role Of Employee Well-beingmentioning
confidence: 99%
See 1 more Smart Citation